Comparing approaches to the management of malignant pleural effusions. (3rd April 2017) - Porcel, José M.; Lui, Macy Mei-Sze; Lerner, Andrew D.; Davies, Helen E; Feller-Kopman, David; Lee, Y.C. Gary
ABSTRACT: Introduction : Management of symptomatic malignant pleural effusions is becoming more complex due to the range of treatment options, which include therapeutic thoracenteses, thoracoscopic talc pleurodesis, bedside pleurodesis with talc or other sclerosing agents via small-bore chest catheters, indwelling pleural catheters, surgery, or a combination of some of these procedures. Areas covered : Recent advances for the expanding range of treatment options in malignant pleural effusions are summarized, according to the best available evidence. Expert commentary : Selection of a treatment approach in malignant pleural effusions should take into account patient preferences and performance status, tumor type, predicted prognosis, presence of a non-expandable lung, and local experience or availability. The role of pleurodesis has decreased with the advent of indwelling pleural catheters, which provide a high degree of symptomatic relief on an outpatient basis and, therefore, are being positioned as a first choice therapy in many centers. Talc poudrage pleurodesis should probably be reserved for those situations in which pleural tumor invasion is discovered during diagnostic thoracoscopy. Ongoing randomized controlled trials will offer solid evidence on which of the available palliative approaches should be selected for each particular patient.